Pengembangan Pembelajaran Ekstrakurikuler Di SDN 036 Ujung Berung Dan SDIT Qordova Berdasarkan Analisis SWOT - Fitria Rayani Rahman; Ghina Fauziah Hazimah; Rani Fitriani; Siti Fatimah (Jurnal Bintang Pendidikan Indonesia, 2023)
The research aims to describe the development of extracurricular learning at SDIT Qordova and SDN 036 Ujung Berung based on the results of the SWOT analysis. This research is a descriptive qualitative research with data collection carried out using interviews, observation, literature and also documentation. The instrument used in this study is a SWOT analysis that considers strengths, weaknesses, opportunities and threats. The results of the study show that the main strength of the two schools is the availability of various types of extracurricular options that facilitate various interests and talents of students. The drawback is the unavailability of facilities from several extracurriculars such as rooms and fields. The main opportunity is the potential of students in non-academic fields to develop so that they have the opportunity to become a quality and achieving school, and the threat is low student participation and attendance in participating in extracurricular activities. The findings and observations made at two schools, namely SDIT Qordova and SDN 036 Ujung Berung, show that the development of extracurricular learning is very important.